Banana Root Borer, Cosmopolites sordidus (Germar) (Insecta: Coleoptera: Curculionidae) - Robert E. Woodruff; Thomas R. Fasulo (EDIS)
EENY-391, a 5-page illustrated fact sheet by Robert E. Woodruff and Thomas R. Fasulo, describes this serious insect pest of bananas with distribution throughout the banana growing regions of the world.  Includes sections on synonymy, distribution, description, life cycle and biology, hosts, management, and selected references. Published by the UF Department of Entomology and Nematology, October 2006.